Kegiatan Mengajar untuk Melatih Pemahaman Murid SD di Desa Petak, Gianyar, Bali - Made Christin Dwitrayani; I Made Bayu Wisnawa; I Ketut Sutapa; Luh Komang Candra Dewi; Gde Herry Sugiarto Asana; Dewiwati Sujadi; I Dewa Ayu Tita Permata Tabita; I Komang Adi Putra Wirawan; Ni Luh Eka Wahyuni; Ni Putu Candra Pratiwi (Prosiding Seminar Nasional Riset dan Pengabdian pada Masyarakat, 2024)
Triatma Mulya University's Thematic Real Work Lecture is one form of implementation of Merdeka Learning Merdeka Campus which is a policy of the Minister of Education and Culture. The Petak Village Elementary School Teaching Program provides new activities for elementary school children in Petak Village when they are bored with their lessons. This Thematic Real Work Lecture activity program is carried out within 3 weeks, namely Monday, January 16, 2024 to February 01, 2024, which is located in Petak Village, Gianyar Regency. Our teaching activities were carried out at SDN 1 Petak, SDN 2 Petak and SDN 3 Petak. The results of the implementation of the Thematic Real Work Lecture in Petak Village Gianyar can be carried out well and as expected This is evidenced by the achievement of all programs that have been implemented. With the teaching at SDN 1 Petak, SDN 2 Petak and SDN 3 Petak will train children's creativity and creation in learning. And children are invited to learn while playing while training their level of focus. We teach self-introduction using English, answering synonyms and antonyms of words, learning while playing, and so on.